Membrane fluidity is involved in the regulation of heat stress induced secondary metabolism in Ganoderma lucidum. (2nd March 2017) - Liu, Yong‐Nan; Zhang, Tian‐Jun; Lu, Xiao‐Xiao; Ma, Bao‐Liang; Ren, Ang; Shi, Liang; Jiang, Ai‐Liang; Yu, Han‐Shou; Zhao, Ming‐Wen
Summary: Ganoderma lucidum has become a potential model system for evaluating how environmental factors regulate the secondary metabolism of basidiomycetes. Heat stress (HS) is one of the most important environmental factors. It was previously reported that HS could induce the biosynthesis of ganoderic acids (GA). In this study, we found that HS increased GA biosynthesis and also significantly increased cell membrane fluidity. Furthermore, our results showed that addition of the membrane rigidifier dimethylsulfoxide (DMSO) could revert the increased GA biosynthesis elicited by HS. These results indicate that an increase in membrane fluidity is associated with HS‐induced GA biosynthesis. Further evidence showed that the GA content was decreased in D9des ‐silenced strains and could be reverted to WT levels by addition of the membrane fluidizer benzyl alcohol (BA). In contrast, GA content was increased in D9des ‐overexpression strains and could be reverted to WT levels by the addition of DMSO. Furthermore, both membrane fluidity and GA biosynthesis induced by HS could be reverted by DMSO in WT and D9des ‐silenced strains. To the best of our knowledge, this is the first report demonstrating that membrane fluidity is involved in the regulation of heat stress induced secondary metabolism in filamentous fungi.